Rapid Detection of Pasteurella multocida Infection by Direct Blood and Tissue Polymerase Chain Reaction in Animals and Poultry - Bhanderi, Bharat B.; Mistry, Sneha J.; Roy , Ashish (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The aim of the present study was rapid detection of Pasteurella multocida infection by direct blood and tissue PCR technique. A total 151 samples comprising of 112 blood samples, 37 tissues samples, one nasal swab, and one bone marrow from various ruminants and poultry were processed by cultural methods and confirmed by PM-PCR by amplifying a product of 460bp. Among them four Pasteurella multocida were obtained from tissue samples of buffaloes and two from poultry and, one from blood sample of cow. The clinical samples were processed for direct blood PCR (n=112 blood, 37 tissue) and direct tissue PCR (n=151) methods. Out of 112 blood samples processed, one blood sample of cow positive for P. multocida by cultural method was also found to be positive by direct blood PCR. Out of 151 samples processed for direct tissue PCR, six tissue samples positive for P. multocida by cultural methods were also found to be positive by direct tissue PCR. Conventional cultural method as well as PM-PCR for identification of P. multocida infection in animals and poultry requires minimum 24-48 hrs for identification, while direct blood and tissue PCR gives specific diagnosis within 3 hrs once the sample is received at laboratory. Thus direct application of PCR on blood and tissues will enable to give rapid diagnosis of P. multocida infection during the outbreaks in animals and poultry.